Recent Smart Methods for Achieving High‐Energy Asymmetric Supercapacitors. Issue 2 (5th December 2017) - Huang, Yalan; Zeng, Yinxiang; Yu, Minghao; Liu, Peng; Tong, Yexiang; Cheng, Faliang; Lu, Xihong
Abstract: With the development of portable electronic equipment, electric vehicle, space technology, and power‐grid and energy‐storage technology, new efficient energy‐storage devices need to be developed urgently. Recently, asymmetric supercapacitors (ASCs) have attracted ever‐increasing interest as one of the most promising energy‐storage devices given their remarkable advantages of wide operation voltage window, high power density, and moderate energy density. However, to meet the needs of the rapid development of electronic equipment, it is necessary to optimize the electrode materials and device design to further boost the energy density of ASCs. In recent years, numerous attempts have been made to improve the energy density of ASC devices by increasing the capacitance and/or enlarging the voltage window. Here, recent smart strategies are highlighted, including the introduction of intrinsic defects, element doping, and surface functionalization to increase the capacitance of the electrode materials, and optimizing the electrolyte and electrode materials, as well as their surface charge, to broaden the voltage of cells. Moreover, the current challenges and future opportunities for the development of high‐performance ASCs are also discussed. Abstract : Recent smart strategies to increase the capacitance of electrode materials and optimize the electrolyte and electrode materials, as well as their surface charge, to broaden the voltage of cells are presented. These include the introduction of intrinsic defects, element doping, and surface functionalization. Moreover, the current challenges and future opportunities for the development of high‐performance asymmetric supercapacitors are also discussed.